Deciphering the complex architecture of an herb using micro-computed X-ray tomography, with an illustrated discussion on architectural diversity of herbs. (25th January 2018) - Chomicki, Guillaume; Staedler, Yannick M; Bidel, Luc P R; Jay-Allemand, Christian; Schönenberger, Jürg; Renner, Susanne S
Abstract: Differing from most animals, plants have an indeterminate body plan, allowing them to add new body parts throughout their lifetime. The realized modular construction of a plant is the result of endogenous processes and exogenous constraints. Plant architectural analysis provides a holistic approach to whole-plant development by disentangling endogenous processes from exogenous constraints. Such analyses have focused more on trees than herbs. We here report a rare growth form discovered in the tropical herb Centella asiatica (Apiaceae) using micro-computed X-ray tomography to understand organogenesis in the meristem. Seeds of C. asiatica germinate to give rise to an orthotropic monochasium (sympodium) with terminal inflorescences. A stolon subsequently emerges from the oldest leaf axils of the sympodium. The primary growth of stolons is indeterminate (monopodial), and they only bear scale leaves. The stolon not only produces new leafy sympodial shoots at each node but also an axillary inflorescence. To place this growth form in context, we illustrate all architectural models so far reported from herbs. Our study highlights the complexity of herb architectures and illustrates the use of a novel methodology to decipher plant branching modes.